2020
DOI: 10.1186/s12939-020-01232-1
|View full text |Cite
|
Sign up to set email alerts
|

Global health activists’ lessons on building social movements for Health for All

Abstract: Background: The People's Health Movement (PHM) was formed in 2000 and drew inspiration from the Alma Ata Declaration on Primary Health Care's 'Health for All' (1978). Since then PHM has been an active part of a global counter-hegemonic social movement. This study aimed to gain insights on social movement building, drawing on the successes and failures reported by activists over their experiences of working in the Health for All social movement to improve health, justice and equity. Methods: Qualitative researc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Power dynamics granted women with lesser power in decision-making ( 30 , 31 ). Abortion is still not accessible in some countries as it is either criminalized or available in restricted circumstances.…”
Section: Examples From the Pastmentioning
confidence: 99%
“…Power dynamics granted women with lesser power in decision-making ( 30 , 31 ). Abortion is still not accessible in some countries as it is either criminalized or available in restricted circumstances.…”
Section: Examples From the Pastmentioning
confidence: 99%
“…There are circumstances or windows of opportunity under which advocacy coalitions are likely to wield power. While global movements have been emphasised,126–129 we found that shifts to a democratised society provide a window of opportunity for citizens to push for reforms36 58 130 particularly if reforms are framed in a way that attracts previously marginalised groups or conflict expansion 131. That a shift to a democratic society underpins citizen participation in health underscores the role of institutions in enabling an advocacy driven policy change.…”
Section: Discussionmentioning
confidence: 87%
“…Dialogical programs convene both service providers and service users, and seek to bring the experiences of the marginalized into mainstream discussion, such as stories about experiences of poor or discriminatory treatment by health providers [116,117,124]. This can be accomplished using various approaches, ranging from human rights education and conscientization to Participatory Action Research [125], developing political capabilities among those communities that disproportionately experience MoW [126], the utilization of formalized processes for civil society engagement in governmental priority setting and program evaluation [76], soliciting in-depth feedback from women following labour and delivery [74], and social accountability or legal empowerment approaches [127,128].…”
Section: Phase 3: Approaches To Addressing Powermentioning
confidence: 99%